Extraction of impacted mandibular third molar with cemental hyperplasia using buccal cortex osteotomy of the mandibular ramus. Issue 2 (March 2021) - Shimizu, Hajime; Ito, Ko; Yamazaki, Fumie; Takahashi, Kosuke; Eda, Takashi; Kondoh, Toshirou
Abstract: Impacted mandibular third molar extraction is one of the most frequent procedures performed in the field of oral surgery. Oral surgeons sometimes face cases that cannot be extracted using the conventional procedure because of atypical tooth structure or irregular tooth position in the mandible. Here, we report an unusual impacted third mandibular molar with atypical root form, which was extracted by buccal cortex osteotomy of the mandibular ramus. A 42-year-old Japanese female presented with a complaint of discomfort in the left molar region. Radiographical examination showed an impacted third molar with a mushroom-like root overlapping the mandibular canal. This lesion was radiographically diagnosed as cemental hyperplasia. The tooth could not be extracted using the conventional procedure, and buccal cortex osteotomy was applied. Briefly, bones necessary for extraction were removed once from the mandibular ramus. After extraction, the bony fragment was repositioned in the original position. The patient experienced no postoperative complications such as nerve paralysis, mandibular angle fracture, and infections. Buccal cortex osteotomy is a simple and easy technique to extract impacted mandibular third molars that cannot be extracted by conventional methods.